2013
DOI: 10.1136/injuryprev-2013-040924
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of the International Classification of Diseases codes to identify abusive head trauma: a feasibility study

Abstract: Objective To assess the accuracy of an International Classification of Diseases (ICD) code-based operational case definition for abusive head trauma (AHT). Methods Subjects were children <5 years of age evaluated for AHT by a hospital-based Child Protection Team (CPT) at a tertiary care paediatric hospital with a completely electronic medical record (EMR) system. Subjects were designated as non-AHT traumatic brain injury (TBI) or AHT based on whether the CPT determined that the injuries were due to AHT. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…9 In that study, which used a similar methodology to ours, the sensitivity and specificity of ICD-9-CM codes for abusive head trauma were 92% and 96%, respectively, similar to our results for TBI of 85% and 92%.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…9 In that study, which used a similar methodology to ours, the sensitivity and specificity of ICD-9-CM codes for abusive head trauma were 92% and 96%, respectively, similar to our results for TBI of 85% and 92%.…”
Section: Discussionsupporting
confidence: 85%
“…7 More recent studies have focused specifically on the coding of physical abuse cases but have been limited because they use data from single children’s hospitals. 8,9 For example, Hooft et al 8 examined the accuracy of ICD-9-CM codes at one children’s hospital and found that the sensitivity of ICD-9-CM codes for abuse was only 77%, but the specificity was 100%; thus, over 20% of abuse cases documented by a physician in the medical record were not coded as abuse in the hospital discharge data. Because coding practices can vary among hospitals, additional studies are needed to assess whether such findings are generalizable to other hospitals.…”
mentioning
confidence: 99%
“…Two studies evaluated the accuracy of ICD-9 codes in child physical abuse and found sensitivities in the 75% to 90% range. 37,38 Furthermore, KID data are not reported every year and skipped 2008, the year that the AHT rate peaked in our study population.…”
Section: Discussionmentioning
confidence: 91%
“…Berger et al [17] tested the accuracy of this approach, retrospectively assessing hospital data at a large tertiary care hospital by using the CDC approach and comparing the outcome with statistics drawn from the hospital child protection program database. The authors found that the ICD 9-based approach yielded a sensitivity of 92% and a specificity of 96%, supporting the use of the CDC's approach.…”
Section: Epidemiology Of Abusive Head Traumamentioning
confidence: 99%